Assessing the effect of Massive Open Online Courses as remedial courses in higher education. Issue 4 (4th July 2022) - Agasisti, Tommaso; Azzone, Giovanni; Soncin, Mara
ABSTRACT: The current study assesses the effect of using Massive Open Online Courses (MOOCs) with the specific goal of providing remedial education. The data refer to an Italian flagship university, Politecnico di Milano, where a MOOC platform was launched following the strategy 'MOOCs to bridge the gaps'. Hence, the study aims at assessing the effect of students completing a MOOC taken as a foundation course in physics on their ability to pass the subsequent on-campus exam in physics (N = 2, 830). The research used Propensity Score Matching (PSM), basing the propensity scores on personal and academic information about the students. The results show that completers are 7 to 16 percentage points more likely to pass the related exam than the other students enrolled in the same MOOCs. These findings support the idea that using MOOCs for remedial purposes is effective in terms of student achievement within a formal education context.